Telepresence robots from the perspective of psychology and educational sciences - Virkus, Sirje; Leoste, Janika; Marmor, Kristel; Kasuk, Tiina; Talisainen, Aleksei (Information and Learning Sciences, 2023)
Purpose Telepresence robots (TPRs) are an emerging field of application and research that have received attention from various disciplines, including computer science, telehealth and education. The purpose of this study is to conduct a bibliometric analysis of publications on TPR in the Web of Science database from 1980 to 2022 to gain a better understanding of the state of research on TPRs and explore the role of pedagogical and psychological aspects in this research. Design/methodology/approach The analysis of research publications on TPRs was made on the basis of papers published in the Web of Science database from 1980 to 2022. The following research questions were proposed: What are the main tendencies in publication years, document types, countries of origin, source titles, publication authors, affiliations of authors and the most cited articles related to TPRs? What are the main topics discussed in the publications from the perspective of psychology? What are the main topics discussed in the publications from the perspective of educational sciences? Findings The results indicate that it is in the computer science where most of the existing research has been conducted, whereas the interest in the psychology and educational science has been relatively low. The greatest regional contributor has been the USA, whereas the effort in the European Union lags behind. Research publications in psychology in the Web of Science database related to TPRs can be grouped into three broad thematic categories: features of TPRs, degree of social presence compared to physical presence or other mediated technologies and opportunities for using TPRs. The results suggest that from the perspective of psychology, TPRs are one of the approaches that could enable greater social presence in remote communication. Most of the analysed papers in educational sciences investigated the opportunities of using TPRs in various educational fields. However, while the findings of the studies indicated significant potential of TPRs for education, their acceptance for wider use is still challenged. Research limitations/implications The limitations of this research are that this study only analysed research papers in the Web of Science database and therefore only covers a limited number of scientific papers published in the field of psychology and educational sciences on TPRs. In addition, only publications with the term “telepresence robots” in the topic area of the Web of Science database were analysed. Therefore, several relevant studies are not discussed in this paper that are not reflected in the Web of Science database or were related to other keywords. Originality/value The field of TPRs has not been explored using a bibliographic analysis of publications in the Web of Science database from the perspective of psychology and educational sciences. The findings of this paper will help researchers and academic staff better understand the state of research on TPRs and the pedagogical and psychological aspects addressed in this research.
Publisher: Emerald Publishing Limited